Effects of visual deprivation and portion size on food-related perception and behavior - Baek, Min Kyung; Shim, Joon Young (Nutrition research and practice, 2025)
Food consumption directly affects human health. Nevertheless, the mechanisms underlying the food portion-size effect related to the visual cues significantly affecting food intake are unclear. This study examined the effects of visual cues on food consumption and satiety. The subjects (16 females and 14 males) were exposed to one of the following 4 experimental conditions for 4 weeks: blindfolded large unit, blindfolded small unit, visible large unit, and visible small unit. The subjects were served 600 mL of a multigrain shake (a single 600 mL cup as a large unit or six 100 mL cups as a small unit). The subjects' food intake was similar under the blindfolded and visible conditions, regardless of the unit size. Under the blindfolded condition, the subjects significantly overestimated their intake when served small units compared to large units (63.50 mL vs. 110.01 mL, < 0.05). Under the visible condition, however, the actual and estimated consumption volumes were similar. In addition, although the participants consumed larger portions when served large units, there was no significant difference in subjective fullness between the 2 portion size conditions. The thirst levels did not vary significantly according to the portion sizes or visibility conditions. Small food units facilitate more effective consumption monitoring through visual cues, which might contribute to reduced food intake. Previous studies on solid foods have revealed significant effects of portion size and visual cues on satiety. Nevertheless, this study, which focused on liquid food, showed no significant differences in satiety despite the variations in perceived fullness across conditions. This suggests that the effect of portion size on satiety may differ according to solid and liquid foods. Considering these findings, future research should examine the mechanisms underlying the portion-size effects in liquid foods with more refined methodologies.